Zinc Binding to S100B Affords Regulation of Trace Metal Homeostasis and Excitotoxicity in the Brain - Hagmeyer, Simone; Cristóvão, Joana S.; Mulvihill, John J. E.; Boeckers, Tobias M.; Gomes, Cláudio M.; Grabrucker, Andreas M. (Frontiers in Molecular Neuroscience, 2018)
Neuronal metal ions such as zinc are essential for brain function. In particular synaptic processes are tightly related to metal and protein homeostasis, for example through extracellular metal-binding proteins. One such protein is neuronal S100B, a calcium and zinc binding damage-associated molecular pattern (DAMP), whose chronic upregulation is associated with aging, Alzheimer’s disease, motor neuron disease and traumatic brain injury. Despite gained insights on the structure of S100B, it remains unclear how its calcium and zinc binding properties regulate its function on cellular level. Here we report a novel role of S100B in trace metal homeostasis, in particular the regulation of zinc levels in the brain. Our results show that S100B at increased extracellular levels is not toxic, persists at high levels, and is taken up into neurons, as shown by cell culture and biochemical analysis. Combining protein bioimaging and zinc quantitation, along with a zinc-binding impaired S100B variant, we conclude that S100B effectively scavenges zinc ions through specific binding, resulting in a redistribution of the intracellular zinc pool. Our results indicate that scavenging of zinc by increased levels of S100B affects calcium levels in vitro. Thereby S100B is able to mediate the cross talk between calcium and zinc homeostasis. Further, we investigated a possible new neuro-protective role of S100B in excitotoxicity via its effects on calcium and zinc homeostasis. Exposure of cells to zinc-S100B but not the zinc-binding impaired S100B results in an inhibition of excitotoxicity. We conclude that in addition to its known functions, S100B acts as sensor and regulator of elevated zinc levels in the brain and this metal-buffering activity is tied to a neuroprotective role.